Russian Federation : Agriculture Support Policies and Performance - World Bank (World Bank, Washington, DC, 2021)
Since 2013, the performance of Russian agriculture can fairly be described as remarkable. On average, Russian agriculture has been growing faster (3.3 percent per year) than gross domestic product (GDP) (0.9 percent per year). Increasing food exports and decreasing imports have led to a fall in the agricultural trade deficit from nearly US27 billion dollars in 2013 to about US5 billion dollars in 2018. As a result of this performance, Russian self-sufficiency targets have been met in all commodities except for milk production. Despite this positive trajectory, Russian agriculture is operating at less than its potential. Several studies have called attention to abandoned land as proof that Russian agriculture is underperforming. Currently, Russia uses just over half of registered agricultural lands (Uzun, 2017a). However, only 5-10 percent of total croplands could feasibly be brought back into production. Moreover, increases in gross agricultural output in OECD countries, as well as in Russia, come overwhelmingly from yield increases and not from increases in area. This report presents a general overview of Russian agriculture performance and policy, focusing on both the achievements of the past few years and the limits to that performance. It begins with a broad survey of production, land use, livestock, productivity and trade (chapter one). It then focuses on policies in the State Program for the Development of Agriculture in Russia, the types of support, distribution of subsidies, and the effectiveness of the Program (chapter two). It then focuses on how Russian support differs from support in OECD and other countries (chapter three). It ends with a conclusion on what can be done for Russian agriculture to operate closer to its potential (chapter four).